Insect Distribution In The Commonity Forest Plantation Of Waya Hamlet, Tehoru Vilage, Tehoru Subdsistrict, Central Maluku Regency - Yusuf Lahadi; Fransina Latumahina; Cornelia Wattimena (Tropical Small Island Agriculture Management, 2025)
This research aims to identify the types of insects found in community forest areas in Dusun Waya, Tehoru Village, Tehoru District, Central Maluku Regency, to analyze the factors influencing the presence of insects in the community forest area, and to evaluate the effectiveness of insect traps in the community forest area of Dusun Waya, Tehoru Village, Tehoru District, Central Maluku Regency. This research was conducted in May 2025. The method used in this study was an inventory method for insect data collection with a transect width of 20 meters and a length of 100 meters with an interval of 10 meters, followed by insect sampling. The results of the study at the research site in Dusun Waya, Tehoru Village, Tehoru District, Central Maluku Regency, recorded 29 insect species classified into 13 orders and 26 families, with a total of 425 individuals along the entire transect. Among the 5 transects, the highest number of insects was found using the hand collecting method, which proved to be the most effective method in this study. Factors affecting the presence of insects include air temperature, humidity, and light intensity.